HUBUNGAN FAKTOR USIA, GENDER, LAMA DUDUK DENGAN KEJADIAN NYERI PUNGGUNG BAWAH PADA KARYAWAN RS HUSADA UTAMA SURABAYA - Octavian, Hasanuddin; Deo Fau, Yohanes; Hargiani, Fransisca Xaveria; Hadi Endaryanto, Agung (NHM PRESS, 2023)
A company needs quality human resources to be able to compete with competitors, so quality human resources are needed. However, if health problems occur, it will reduce the quality of work of human resources. One of the health problems that affects work is low back pain (LBP), Caused, among other things by immobile back muscles and continuously over a long period of time. Husada Utama Hospital Surabaya employee spending time sitting while working for 4-6 hours a day can increase the risk of experiencing LBP. Other factors that are at risk of had a LBP are age, gender, and Sitting for long periods. This study aims to determine the relationship between Age, Gender, Long Sitting and the incidence of LBP in employees at Husada Utama Hospital, Surabaya. Using the quantitative descriptive method with a cross-sectional research design. Researchers used a Roland Morris questionnaire which was distributed to respondents. The sample in this study was 234 employees of Husada Utama Hospital, Surabaya, whose work pattern was dominated by a sitting position. The Results, there was a relationship between the long sitting factor and the incidence of LBP with a p-value of 0.001<0.05 for long sitting with the incidence of acute LBP and p-value 0.00 < 0.05 for long sitting with the incidence of chronic LBP. However, this is inversely proportional to the factors age and gender explained that there was no relationship between age and gender factors and the incidence of low back pain in employees at Husada Utama Hospital, Surabaya.